2020
DOI: 10.13106/jafeb.2020.vol7.no10.929
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Service Quality Toward Student Satisfaction and Loyalty in Higher Education

Abstract: This study analyzes the effect of quality of services provided to the students' in relation to their satisfaction and loyalty. Respondents in this study were seventh semester students of Universitas Muslim Nusantara Al-Washliyah, the total number of students was 312. Data analysis techniques in this study used was SEM (Structural Equation Modeling) using the SmartPLS program. The results showed that students' satisfaction significantly mediated the correlation between academics and students' loyalty, between n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 18 publications
5
24
0
7
Order By: Relevance
“…It was in line with the result of the hypothesis testing that institutional image positively and significantly influenced student satisfaction in Senior High School Education. This finding was in line with a study by (Appuhamilage & Torii, 2019;Bakrie et al, 2019;Hassan et al, 2019;Leonnard et al, 2014;Lunarindiah, 2018;Mulyono et al, 2020;Shahsavar & Sudzina, 2017). The better the image built by Senior High School Education, it might increase student satisfaction.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…It was in line with the result of the hypothesis testing that institutional image positively and significantly influenced student satisfaction in Senior High School Education. This finding was in line with a study by (Appuhamilage & Torii, 2019;Bakrie et al, 2019;Hassan et al, 2019;Leonnard et al, 2014;Lunarindiah, 2018;Mulyono et al, 2020;Shahsavar & Sudzina, 2017). The better the image built by Senior High School Education, it might increase student satisfaction.…”
Section: Discussionsupporting
confidence: 88%
“…The better the image of the educational institution is, student satisfaction will get better. It is in line with a study by (Appuhamilage & Torii, 2019;Bakrie et al, 2019;Hassan et al, 2019;Leonnard et al, 2014;Lunarindiah, 2018;Mulyono et al, 2020;Shahsavar & Sudzina, 2017). The good image of an educational institution can also stimulate student loyalty.…”
Section: Literature Reviewsupporting
confidence: 87%
“…EFA was used to unveil the factors of non-academic service quality. Previous studies, using students as studied objects, have revealed a positive association between non-academic service quality and satisfaction and loyalty (see Kardoyo et al, 2019;Mulyono et al, 2020;Sultan & Yin Wong, 2013). Subsequently, these factors were used to answer our main research hypotheses, which expect non-academic service quality elements to significantly increase parent satisfaction and loyalty.…”
Section: Non-academic Service Qualitymentioning
confidence: 99%
“…Una consecuencia de la acreditación institucional refiere a la opinión de la ciudadanía acerca de las instituciones de educación superior, ya que se plantea como garantía pública de calidad. Particularmente en el caso de las universidades privadas, la acreditación genera una suerte de homologación o mejora competitiva (Mulyono et al, 2020) respecto a las universidades tradicionales.…”
Section: El Sistema De Educación Superior Chileno Y La Acreditación Institucionalunclassified
“…A su vez, contar con financiamiento debiera traducirse en una menor deserción por motivos financieros (Himmel, 2002). Por otra parte, los estudiantes que se integran a una institución que pierde la acreditación no pueden postular a financiamiento estatal, mientras que los estudiantes antiguos pierden la posibilidad de postular a financiamiento del que no sean beneficiarios de antemano; y 2) La pérdida de acreditación tendría un fuerte impacto negativo en la imagen institucional, vale decir, en la percepción del público y de los propios estudiantes respecto de la calidad de la formación impartida en una institución determinada (Mulyono et al 2020).…”
Section: Introductionunclassified